Level Of Effectiveness And Contribution Of Rural And Urban Land And Building Taxes To Regional Original Income - Abid Imanul Akmal; Galih Wicaksono; Boedijono Boedijono (Journal of Business and Economics Research (JBE), 2022)
The Rural and Urban Land and Building Tax (PBB-P2) is one of the strategic taxes for local governments, including the Jember Regency Government. This is because PBB-P2 revenue contributes to Regional Original Income (PAD), so it is necessary to know the level of effectiveness on PAD, as the purpose of this study. This type of research is descriptive, which explains the conditions based on the results of the analysis, with the data source in the form of secondary data. In general, this study resulted in the findings that the effectiveness of PBB-P2 in the less effective category, and its contribution to PAD at the very low level or category. The recommendation from the results of this study is that the Jember Regency Government should always strive to increase the target and realization of PBB-P2 revenue in accordance with its potential, so that it can contribute maximally to PAD.